(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: For a significant period, online patient support groups have served as platforms for disseminating health-related information and providing assistance. Their importance has further increased with the advent of the internet. Objectives: This paper aims to achieve a deeper understanding of the literature concerning Online Patient Support Groups health information through the use of bibliometric analysis. Methods: The study conducts a bibliometric analysis of Online Patient Support Groups using literature sourced from PubMed. It utilizes profile research networking software and Vosviewer from Harvard University. Discussion: It is clear that Online Patient Support Groups hold greater importance for marginalized communities. Health care providers and regulators must be vigilant to prevent any negative consequences. Conclusion: The findings underscore the significance of Online Patient Support Groups in public health, with video and audio content being more frequently cited than journal articles. Despite a notable increase in publications in 2020, the number of researchers in this field remains limited.